Research Ideas and Outcomes journal (R.I.O.): A novel way to make science - Hachani, Samir (Septentrio Conference Series, 2017)
Watch the VIDEO here. Peer review has been a cornerstone of science since the first scientific journals started in the middle of 17th century. It has since evolved from a case by case and non standardized process to a more regulated and organized undertaking. The period at which peer review entered its new phase is the Second World War and the extraordinary boom of scientific output that resulted from the cold war. All this output had to have a receptacle (scientific journals) but also had to be selected due to the big amount of data produced. That is when peer review became unanimously and, to some extent, uniformly implemented. It also became the unavoidable door leading to a number of advantages all researchers are looking for (promotions, funding, prize, etc.).That’s when the human component intervened and made the process a rather biased process subject to all kinds of critics. One of the main (if not the main) problem is the secrecy in which the process is undertaken and that has led to all kind of iniquitous, unjust and sometimes bizarre decisions. The process tried to inject some kind of openness (going from blind to double blind peer reviewing for example) with little results. The 90’s of the last century saw the Internet slowly becoming more and more used in everyday life and, more importantly, in the scientific and academic research. With all the problems besetting peer review ,Internet’s openness seemed as the best cure to all the grievance peer review elicited. Among the most revolutionary experiences, Faculty of 1000 (F 1000), Atmospheric Chemistry and Physics (A.C.P.), Journal of Medical Internet Research (J.M.I.R.), British Medical Journal? Electronic Transactions on Artificial Intelligence ( ETAI) and Biology Direct have introduced new ways to undertake peer review that have somehow alleviated the numerous critics. With Research Ideas Outcomes (RIO), the process enters a new era of openness as its two stages are completely open: the pre submission peer review (part 1) in which the submitter is reviewed before submission by a colleague and could even ask colleagues to help write his proposal and then open post-publication peer-review (part 2) in which the process is even more open as authors could decide what reviews are published, when and also decide to ask for an in house classic type of review done exclusively by peer reviewers from RIO or let the whole community implement a Post Publication Peer Review that could putatively last as long as the article is on the system. All the process is open in all its steps and allows novelty, among others, to recognize namely reviewers’ work, a task they have so far anonymously and without any reward of any kind. This proposal will explain in details the process and try to understand the (r)evolution this kind of process introduces to the making of science through transparency in a stage of science that has been known to be utterly secretive.